Fabrication and Magnetic Properties of \(\text{Nd}_2\text{Fe}_{14}\text{B/Fe}_{65}\text{Co}_{35}\) Hard Magnetic Ribbons - Truong, Nguyen Xuan; Khanh, Nguyen Van (Communications in Physics, 2013)
Nd\(_2\)Fe\(_{14}\)B/Fe\(_{65}\)Co\(_{35}\) hard magnetic ribbons were fabricated by melt-spinning technique using Nd\(_{16}\)Fe\(_{76}\)B\(_{8 }\) and Fe\(_{65}\)Co\(_{35}\) pre-alloys as starting materials. The results showed that the formation of the interactive hard/soft nanocomposite with the homogeneous distribution of the Fe-Co phase throughout the Nd\(_{2}\)Fe\(_{14}\)B matrix provided the Curie temperature (\(T_{c})\) as high as 747 K, the magnetic remanence (B\(_{r}\)) of 8.88 kG and the maximum energy product, (BH)\(_{\max}\), of 16.75 MG.Oe for the fabricated Nd\(_{2}\)Fe\(_{14}\)B/Fe\(_{65}\)Co\(_{35}\) ribbons at the optimal speed of 25 m/s. In addition, the intrinsic coercivity (\(_{i}\)H\(_{c}\)) of 9.27 kOe and remanence coercivity (\(_{b}\)H\(_{c}\)) of 6.94 kOe were found for these ribbons. The roles of the soft Fe\(_{65}\)Co\(_{35}\) phase in the increasing of \(T_{c}\), \(B_{r}\) as well as in the (00l) preferred crystallographic orientation of hard magnetic grains on the free surface side of the fabricated ribbons were also discussed.